A mídia impressa sergipana nas eleições para governador em 2006: cobertura do Cinform, correio de Sergipe e jornal da cidade - Dias, Deise Ribeiro (2010)
The elections for governor in 2006 with its victory Marcelo Déda Workers Party (PT), were a landmark in the state of Sergipe, for the first time, called progressive fronts (an alliance of parties formed mostly by origin of the left) broke the hegemony of two political groups, Franco and the Alves, whose direction was in force for over 30 years. This study proceeds on the assumption that the print media has certain standards of conduct in covering the election period. Therefore, this study seeks to quantify, classify and compare data from three newspapers more representative of the State of Sergipe (Cinform, Cidade Journal and Correio de Sergipe) to analyze the behavior of these journals, such as private apparatus of hegemony in election coverage 2006. It also uses the concept of hegemony Gramsci and theories of journalism framing (Entman and Porto) and agenda setting (McCombs and Shaw) to identify these patterns